Are dietary patterns in childhood associated with IQ at 8 years of age? A population-based cohort study. Issue 7 (7th February 2011) - Northstone, Kate; Joinson, Carol; Emmett, Pauline; Ness, Andy; Paus, Tomáš
Abstract : Background: Little is known about the effects of overall diet in childhood and intelligence later in life. Methods: The current study, based on the Avon Longitudinal Study of Parents and Children, uses data on children's diet reported by parents in food-frequency questionnaires at 3, 4, 7 and 8.5 years of age. Dietary patterns were identified using principal-components analysis and scores computed at each age. IQ was assessed using the Wechsler Intelligence Scale for Children at 8.5 years. Data on a number of confounders were collected, and complete data were available for 3966 children. Results: After adjustment, the 'processed' (high fat and sugar content) pattern of diet at 3 years of age was negatively associated with IQ assessed at 8.5 years of age—a 1 SD increase in dietary pattern score was associated with a 1.67 point decrease in IQ (95% CI −2.34 to −1.00; p<0.0001). The 'health-conscious' (salad, rice, pasta, fish, fruit) pattern at 8.5 years was positively associated with IQ: a 1 SD increase in pattern score led to a 1.20 point increase in IQ (95% CI 0.52 to 1.88; p=0.001). Conclusion: There is evidence that a poor diet associated with high fat, sugar and processed food content in early childhood may be associated with small reductions in IQ in later childhood, while a healthy diet, associated with high intakes of nutrient rich foods described at about the time of IQ assessment may be associated with small increases in IQ.